Simulation model of crop yields - Logachev, Maxim; Goncharov, Dmitrii (BIO web of conferences, 2024)
The article identifies the factors that affect the yield of crops grown in the open ground. Most factors are random in nature, which depending on a variety of conditions can positively or negatively affect crop growth processes. To predict the strategy for growing plants to maximize possible yield requires the development of simulation models that allow repeated virtual experiments, taking into account changes in a variety of parameters. This justifies the need for the study to be conducted. The use of structural analysis methods allowed to establish key objects and processes affecting all stages of plant development, to determine the links between them and the rules of interaction. Based on this, a model of system dynamics was developed, reflecting the processes of plant transition from one state to another, and the parameters affecting the speed of such transition. The developed model can be used as the basis for an expert system that manages agricultural processes.